Oct4 Gene Expression in Primary Colorectal Cancer Promotes Liver Metastasis - Shiki Fujino; Norikatsu Miyoshi (Hindawi Limited, 2019)
Purpose. The Oct4 gene plays an important role in undifferentiated embryonic stem cells and regulates stem cell pluripotency. The aim of this study was to examine the relationship between Oct4 expression and liver metastasis of colorectal cancer (CRC) in clinical samples and investigate the role and abilities of Oct4-positive CRC cells. Methods. The study included 158 patients who underwent surgery for CRC between 2009 and 2011. The correlations between the Oct4 gene expression and the clinical parameters were assessed, and liver metastasis-free survival (LMFS) was evaluated in these patients. Oct4-EGFP-positive cells were established to examine their subpopulation and ability. The capacity to form liver metastasis in vivo was examined using CRC cell lines and primary cultured CRC cells. Results. LMFS was significantly poor in the Oct4 high-expression group compared with the low-expression group (P=0.008). Multivariate analyses showed that Oct4 expression (P=0.015) and TNM stage (P<0.001) were significantly correlated with LMFS. Oct4-EGFP-positive cells highly expressed stem cell-associated markers and had self-renewal and differentiation abilities. Oct4-high cells actively formed liver metastasis. Conclusion. The Oct4 expression was correlated with liver metastasis in CRC patients. Oct4 expression cells have self-renewal and differentiation abilities like those of cancer stem cells. Oct4 contributed to forming liver metastasis in CRC.